Uji Adaptasi Galur-Galur Tanaman Sorgum di Lahan Kering Kota Palembang - Karlin Agustina; Haris Kriswantoro; Evriani Mareza; Yursida Yursida; Desta Wirnas (Universitas Sebelas Maret, 2025)
Sorghum is a cereal plant that has great potential to be developed in Indonesia as a food crop, feed, and biofuel. Sorghum breeding has resulted in a variety of adaptive lines being developed on dry land. This study aimed to determine the adaptability of sorghum in dry land of Palembang City. The research was conducted in Sukamulya Village, Palembang City, from May to October 2021. The experimental design was arranged using non-factorial Randomized Block Design with treatment of various sorghum lines from IPB breeding, consisting of 11 various lines: A-18-12-7-5 (G1), A-19-18-3-8 (G2), B-14-25-5-6 (G3), B-043-16-5-5 (G4), B-4-6-7 (G5), C-248-16-5-3-4 (G6), C-267-18-18-2-7 (G7), C-375-17-5-9 (G8), Bioguma 1 (G9), Super 6 Agritan (G10), dan Samurai 2 (G11), each treatment was repeated 3 times. The Honestly Significance Difference (HSD) test showed that there were significant differences in plant height, number of leaves, flowering age, harvest age, panicle wet weight, panicle dry weight, 1000 seeds weight, and productivity. C-375-17-5-9 and Bioguma 1 were lines which were able to adapt well on dry land, because overall they showed better agronomic characters than other sorghum lines. The correlation between the characters of the growth component and the yield component showed that the number of leaves, panicle weight and 1000 seeds weight could be used as estimating indicators in selection activities for the improvement of sorghum yield.